ENZYME-SECRETING ACTIVITY OF THE SALIVARY GLANDS IN PREGNANT WOMEN WITH PHYSIOLOGICAL PREGNANCY AND GESTOSIS (World Bulletin of Public Health, 2025)
The article examines the enzyme-secreting activity of the salivary glands in pregnant women with physiological pregnancy and gestosis. The study analyzes the levels of amylase, lipase, pepsinogen, and total protein in saliva. It was found that salivation volume and total protein remain at the control group level, while the activity and output of amylase, lipase, and pepsinogen increase. These changes are more pronounced in women with gestosis. The results suggest that saliva analysis can be used for diagnosing the functional state of the gastrointestinal glands in pregnant women.
Keywords: pregnancy; gestosis; saliva; salivary glands